2019
DOI: 10.3390/ijms20143432
|View full text |Cite
|
Sign up to set email alerts
|

AtCRK5 Protein Kinase Exhibits a Regulatory Role in Hypocotyl Hook Development during Skotomorphogenesis

Abstract: Seedling establishment following germination requires the fine tuning of plant hormone levels including that of auxin. Directional movement of auxin has a central role in the associated processes, among others, in hypocotyl hook development. Regulated auxin transport is ensured by several transporters (PINs, AUX1, ABCB) and their tight cooperation. Here we describe the regulatory role of the Arabidopsis thaliana CRK5 protein kinase during hypocotyl hook formation/opening influencing auxin transport and the aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 70 publications
(185 reference statements)
0
28
0
Order By: Relevance
“…Among others, the D6PROTEIN KINASE and PINOID/WAG AGCVIII kinases are types of kinases that are known to activate the PIN-mediated auxin efflux [65]. Previously, we have shown that the AtCRK5 kinase can phosphorylate in vitro the hydrophilic loops of various PIN proteins, like PIN2 and PIN3 [57,59]. Based on in vitro kinase assays and phospho-peptide analysis data, here we also report the possible phosphorylation sites of AtCRK5 in PIN1, PIN4, and PIN7.…”
Section: Atcrk5 Is a General Regulator Of Auxin Distribution Potentiamentioning
confidence: 66%
See 4 more Smart Citations
“…Among others, the D6PROTEIN KINASE and PINOID/WAG AGCVIII kinases are types of kinases that are known to activate the PIN-mediated auxin efflux [65]. Previously, we have shown that the AtCRK5 kinase can phosphorylate in vitro the hydrophilic loops of various PIN proteins, like PIN2 and PIN3 [57,59]. Based on in vitro kinase assays and phospho-peptide analysis data, here we also report the possible phosphorylation sites of AtCRK5 in PIN1, PIN4, and PIN7.…”
Section: Atcrk5 Is a General Regulator Of Auxin Distribution Potentiamentioning
confidence: 66%
“…The localization and activation of the various PIN proteins are known to be affected by their phosphorylation status [15,[63][64][65]. We have already published that AtCRK5 phosphorylates the PIN2 and PIN3 auxin efflux transporters and this may have a role in the gravitropic response of the Arabidopsis root upon gravistimulation and the hypocotyl hook bending during skotomorphogenesis [57,59]. The decreased abundance of PIN1-GFP, PIN4-GFP, and PIN7-GFP in Atcrk5-1 mutant embryos might reflect a defect in PIN protein stability and/or localization.…”
Section: Atcrk5 Can Phosphorylate the Auxin Efflux Proteins Pin1 Pinmentioning
confidence: 99%
See 3 more Smart Citations